2022
DOI: 10.3390/foods11111588
|View full text |Cite
|
Sign up to set email alerts
|

Storage Stability of Conventional and High Internal Phase Emulsions Stabilized Solely by Chickpea Aquafaba

Abstract: Aquafaba is a liquid residue of cooked pulses, which is generally discarded as waste. However, it is rich in proteins and, thus, can be used as a plant-based emulsifier to structure vegetable oil. This study investigates chickpea aquafaba (CA) as an agent to structure different oil phase volumes (Φ) of canola oil (CO). CO was structured in the form of conventional emulsions (EΦ65% and EΦ70%) and high internal phase emulsion (HIPE) (EΦ75%) by the one-pot homogenization method. Emulsions were evaluated for a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In the study of Buhl et al [ 15 ], the authors analyzed the emulsifying properties of CA by the emulsifying activity index (EAI) and the emulsifying stability index (ESB) of the emulsions prepared with the canned aquafaba at various pH values (i.e., 3, 4.5, 6, 7, and 8.5) and reported that the best EAI and ESB was at pH ≥ 6. This indicates that the natural pH of CA is suitable for preparing stable CA-based emulsions, which was confirmed in the study of [ 14 ].…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…In the study of Buhl et al [ 15 ], the authors analyzed the emulsifying properties of CA by the emulsifying activity index (EAI) and the emulsifying stability index (ESB) of the emulsions prepared with the canned aquafaba at various pH values (i.e., 3, 4.5, 6, 7, and 8.5) and reported that the best EAI and ESB was at pH ≥ 6. This indicates that the natural pH of CA is suitable for preparing stable CA-based emulsions, which was confirmed in the study of [ 14 ].…”
Section: Resultssupporting
confidence: 66%
“…The chickpea seeds were prepared as in [ 14 ]. In short, the chickpea seeds were pre-soaked (16 h at 4 °C) at a ratio of chickpea (C): distilled water (DW) of 1:3 ( w / v ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations